BENTUK PHYSICAL TOUCH NABI MUHAMMAD SAW TERHADAP ASPEK PERKEMBANGAN ANAK USIA DINI - Kholifatun, Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The best example for mankind is the Prophet Muhammad, as a prophet of the last days as well as a role model for his people, all the words and actions taken are examples. The Prophet Muhammad has set an example in all aspects of his life, including in terms of treating early childhood. The research aims to describe the form of physical touch that the Prophet Muhammad PBUH does to young children and examine the benefits of physical touch on aspects of early childhood development. The type of research used is library research. Data collection uses documentation techniques from books and journals, then processed with the data reduction stage, namely searching for data relevant to the research theme, data presentation, namely presenting data that has been collected, and data verification, namely selecting data that is in accordance with the focus of the research. The results of the study stated that the forms of physical touch carried out by the Prophet Muhammad PBUH included kissing, carrying, hugging, stroking and playing together. Aspects of early childhood development that can be stimulated by physical touch include social-emotional, cognitive, physical, motor, social, emotional regulation and the formation of family bonds